Preimplantation genetic diagnosis for cystic fibrosis: a case report - Biazotti,Maria Cristina Santoro (2015)
Cystic fibrosis is an autosomal recessive disorder caused by mutations in the cystic fibrosis transmembrane conductance regulator gene. This disorder produces a variable phenotype including lung disease, pancreatic insufficiency, and meconium ileus plus bilateral agenesis of the vas deferens causing obstructive azoospermia and male infertility. Preimplantation genetic diagnosis is an alternative that allows identification of embryos affected by this or other genetic diseases. We report a case of couple with cystic fibrosis; the woman had the I148 T mutation and the man had the Delta F508 gene mutation. The couple underwent in vitro fertilization, associated with preimplantation genetic diagnosis, and with subsequent selection of healthy embryos for uterine transfer. The result was an uneventful pregnancy and delivery of a healthy male baby.